PHYSICOCHEMICAL STUDY OF CEDAR BARK ETHANOL LIGNIN - Kazachenko , Alexander Sergeevich; Maliar, Yuri Nikolaevich; Levdansky, Alexandr Vladimirovich; Fetisova, Olga Yurievna; Ionin, Vladislav Alexandrovich (Химия растительного сырья, 2025)
This study presents the results of a comprehensive physicochemical study of ethanol lignin isolated from Siberian cedar bark performed under subcritical (190 °C, 60% ethanol) and supercritical (250 °C, 96% ethanol) processing conditions. The aim of the work was to study the effect of temperature and extraction conditions on the structural, molecular and thermal properties of lignin. The intrinsic structure properties of the isolated lignin was investigated by modern physico-chemical analysis methods, including IR spectroscopy, NMR spectroscopy, gel permeation chromatography (GPC) and thermogravimetric analysis (TGA). The registered IR-spectra revealed significant changes in the lignin structure obtained with higher processing temperature. In particular, an increase in the intensity of the absorption units associated with carboxyl groups (1706 cm-1) was observed, indicating the oxidation of phenylpropane structures. The results registered by gel permeation chromatography, allowed to announce that the higher temperature of isolation leads to a shift in the molecular weight distribution towards higher molecular weights. Such results, obviously, connected with an intensification of the extraction of more complexed lignin structures. The polydispersity of the isolated samples also increases, indicating the heterogeneity of the lignin structure obtained at higher temperatures. The results of thermogravimetric analysis reveals that the main process of thermal decomposition of lignin occurs in the 150–500 °C temperature range. The ethanol lignin sample isolated at 250 °C characterized by higher thermal stability and a mass of coke residue at 700 °C in comparison to the sample isolated at 190 °C. This may be due to an increase in the molecular weight of the sample due to the condensation of fragments in the lignin structure, which makes it more resistant to thermal decomposition. The main structural units of lignin, including β-aryl ethers, pinoresinols, phenylcoumarans and guaiacyl units, were identified by 2D NMR HSQC spectroscopy. With increasing processing temperature, the destruction of β-aryl ether bonds and an increase in the number of condensed aromatic structures are observed, which confirms the condensation processes of lignin. This may be due to the homolytic decomposition of labile bonds with subsequent formation of more stable structures.